Harmonizing the Iddah Period for Women Divorced Outside the Court According to KHI and Fiqh Law - Farid, Diana; Abdulah Pakarti, Muhammad Husni; Mabruri, Kemal Al Kautsar; Kusmardani, Alex; Lestari, Elly (JUSTISI, 2024)
Legal harmonization determining the iddah period for divorced women outside of court between Law No. 1 of 1974 and the Compilation of Islamic Law is still an unresolved issue in Indonesia. This study aims to identify the differences and similarities between the two laws, as well as provide recommendations on the proper harmonization of laws for divorced women outside the court. This study uses comparative analysis methods and interviews with Islamic jurists. The results of the study show that there are differences in determining the iddah period between the two laws, and the proper harmonization of law by enforcing Islamic law that is in line with the social and cultural context of Indonesian society. It is hoped that the results of this research can become input for legislators and the public in formulating legal policies that are fair and in accordance with Islamic teachings and the social context in Indonesia.